PUSAT KEBUDAYAAN TIONGHOA SUNGAI KAKAP - Hermawan, Yogi Ikhsan; Nurhamsyah, Muhammad; Caesariadi, Tri Wibowo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
The existence of ethnic Chinese has existed for a long time and is inseparable. The Kakap River area, especially in the old temple area, Sungai Kakap Village, Sungai Kakap District, Kubu Raya Regency is one of the areas inhabited by many ethnic Chinese. Through the potential and problems that exist in the region, it is necessary to make efforts to preserve culture because Chinese culture in West Kalimantan is currently one of the ethnicities that has been recognized and has developed for a long time. Therefore, it is necessary to build a Chinese Cultural Center as a form of development of culture and art and improve the image of the region. Based on potential and problems, the five-step method in design is used by utilizing information from data collection obtained, and supported by clear analysis and synthesis of concepts. This design has the main function as a performance of Chinese cultural and artistic activities as well as supporting functions as building support functions such as cultural research, seminars, and recreation. The result of this design is a design building consisting of a new mass area and an existing mass area with the function of worship, activities, and preservation of Chinese culture. The design theme uses a neo-vernacular architectural approach that adapts to the pattern of the surrounding environment as original architecture built by the local community with a new concept that applies cultural and environmental elements expressed in the form of architectural physical.